European clinical practice guideline: managing and treating laryngopharyngeal reflux disease - Lechien, Jerome R; Chiesa-Estomba, Carlos-Miguel; Hans, Stéphane; Nacci, Andrea; Schindler, Antonio; Bohlender, Jorg E; Runggaldier, Daniel; Crevier-Buchman, Lise; Oguz, Haldun; Zelenik, Karol; Tedla, Miroslav; Siupsinskiene, Nora; et al. (European archives of oto-rhino-laryngology, 2024)
OBJECTIVE: To propose a European consensus for managing and treating laryngopharyngeal reflux disease (LPRD) to guide primary care and specialist physicians. METHODS: Twenty-three European experts (otolaryngologists, gastroenterologists, surgeons) participated in a modified Delphi process to revise 38 statements about the definition, clinical management, and treatment of LPRD. Three voting rounds were conducted on a 5-point scale and a consensus was defined a priori as agreement by 80% of the experts. RESULTS: After the third round, 36 statements composed the first European Consensus Report on the definition, diagnosis, and treatment of LPRD. The hypopharyngeal-esophageal multichannel intraluminal impedance-pH monitoring is the gold standard for diagnosing LPRD (> 1 pharyngeal reflux event) and treating the LPRD with personalized therapy. The empirical treatment needs to be based on diet, stress reduction, and alginates or antiacids to address the acidic and alkaline reflux events. Proton pump inhibitors are kept for patients with acidic LPRD and gastroesophageal reflux disease (GERD) findings. The treatment needs to be as short as possible (minimum two months). The medication can be progressively reduced for patients with relief of symptoms. Changing medication class can be considered for refractory LPRD rather than an increase in drug doses. CONCLUSION: A consensus endorsed by the Confederation of European Otorhinolaryngology-Head and Neck Surgery Societies is presented to improve the management and treatment of LPRD. The approved statements could improve collaborative research through the adoption of common management approaches to LPRD.
Keywords: Head neck surgery; European; Otolaryngology; Consensus; Laryngopharyngeal; Reflux; Guidelines; Gastroesophageal; Europe